Effect of solution pH, precursor ratio, agitation and temperature on Ni-Mo and Ni-Mo-O electrodeposits from ammonium citrate baths - To, Dung T.; Park, Sun Hwa; Kim, Min Joong; Cho, Hyun-Seok; Myung, Nosang V. (Frontiers in Chemistry, 2022)
The induced co-electrodeposition of Ni and Mo is a complex process, where metallic Ni-Mo alloys and Ni-Mo-O composites can originate from the complete and partial reduction of Mo respectively. By adjusting electrolyte compositions and electrodeposition parameters, various metallic, metal/oxide composite, and oxide thin films of Ni-Mo and Ni-Mo-O were electrodeposited from ammonium citrate baths. Ni-ammonia complexes, which play a critical role in promoting the deposition of metallic Ni-Mo alloys, were enhanced at alkaline pH (i.e., 8–10) and lower temperature (i.e., 25–45°C). Moreover, the electrochemical reduction of Ni is under mass transfer limitation, so the deposited Mo content decreased with increasing agitation. On the other hand, higher Mo content can be achieved by relatively higher citrate concentration and larger Mo-to-Ni precursor molar ratio. However, a critical molar ratio of metal precursor resulted in transition from alloy to composite due to Ni inducing the reduction of Mo.